The effectiveness of sexual skills training on improving self-control, empathy and marital satisfaction of married women in Shiraz - Refaee, Maryam; Fereyduni , Samad (Psychology of Woman Journal, 2022)
Family is one of the main elements and institutions related to human factors and emotional and spiritual needs. One of the factors in consolidating married life is paying attention to sexual issues. The aim of the present study was to determine the effectiveness of sexual skills training on improving self-control, empathy, and marital satisfaction of married women in Shiraz. For this purpose, among all the married women of Shiraz city, women who were referred to psychological centers under the supervision of welfare in the quarter of June to August 2020, 30 people were purposefully selected as a statistical sample. The current research design was pre-test-post-test and one-month follow-up, in which sexual skills were investigated as an independent variable (intervening factor) and self-control, empathy, and marital satisfaction as dependent variables. The sexual skills training protocol was implemented in eight 90-minute group counseling sessions. The tools used in this research were self-control, empathy, and marital satisfaction questionnaires. The results showed that the level of marital satisfaction was 0.957, empathy was 0.720, and self-control was 0.875. Therefore, sexual skills training has been effective. Using this training, couples’ marital satisfaction, empathy, and self-control can be increased.